(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
The research deals the evaluation of buckling behavior for 5056-H18 Al alloy columnsunder variable loads and studies the effect of initial deflection on the critical buckling load.Seven samples were used for the purpose of testing the buckling of the column. The criticaldeflection of the column can be determined by measuring a length multiplied by 0.01 andthis is the critical load of the columns. For the purpose of measuring the critical deviation ofthe column, a digital dial gauge has been applied and it set at 0.7 distance from the length ofthe column from the fixed condition. The experimental results were compared with thePerry - Robertson formula, Euler's theory for long columns and with the values calculatedfrom the ANSYS 17 program. It has been observed that the Euler formula showed goodcompatibility with the practical results with safety factor 1.5. The ANSYS results showedwell agreement taking a 1.5 factor of safety. While the Perry-Robertson formula needs a 1.4safety factor to be safe results compared with experimental results.